Miscellaneous theological works of Emanuel Swedenborg - Swedenborg, Emanuel (American Swedenborg Printing and Pub. Society, 1915)
The New Jerusalem and its heavenly doctrine.-- A Brief exposition of the doctrines of the New church.--The Intercourse between the soul and the body.--The white horse mentioned in the Apocalypse, chap. XIX.--Appendix to the treatise of the white horse.--The earths in the universe.--The last judgment.--Continuation concerning the last judgment.